Role conflict and rapid socio-economic change: breastfeeding among employed women in Thailand - Yimyam S. (2014)
Conflicts between women's productive and reproductive roles are intensified by rapid development and social change. Women have a right to offer optimum nutrition to their babies through breastfeeding; they also are entitled to seek gainful employment. For many, furthermore, employment is essential to the economic survival of their families. This article derives from a combined qualitative and quantitative study conducted in Chiang Mai, Thailand. Interviews were carried out with 313 women to investigate the experiences of those who resumed employment within six months after delivery. The findings demonstrate that urban women in the modern workplace face many obstacles in their efforts to maintain lactation while simultaneously undertaking paid work. Current public policies do not address these obstacles effectively, which is of particular concern in today's volatile economic climate.